A monograph of the genus Polylepis (Rosaceae) - Boza Espinoza, T.E.B.; Kessler, M. (Pensoft Publishers, 2022)
We present a monograph of the high Andean tree genus Polylepis (Rosaceae), based on a species concept considering morphological, climatic and biogeographic distinctness as indicators of evolutionary independence. In total, we recognize 45 species of Polylepis , grouped in five sections. Polylepis sect. Sericeae is represented by 15 species in four subsections, P. sect. Reticulatae by seven species, P. sect. Subsericantes by three species, P. sect. Australes by two species and P. sect. Incanaee by three subsections with 18 species. We describe seven new species, one from Colombia ( P. frontinensis ), one from Ecuador ( P. simpsoniae ) and five from Peru ( P. acomayensis , P. fjeldsaoi , P. occidentalis , P. pilosissima and P. sacra ). Three species from Peru ( P. albicans , P. pallidistigma and P. serrata ) are re-instated as valid species. Two taxa from Bolivia ( P. incanoides and P. nana ) are elevated from subspecies to species rank. The morphology, habitat, distribution, ecology and conservation status of each species are documented. We also provide an identification key to the species of the genus and general introductions on taxonomic history, morphology, evolution, ecology and conservation.
Keywords: Subspecies; Biology; Taxon; Ecology; Habitat; Genus; Rosaceae; Taxonomy (biology); Botany; Key (lock); Zoology; https://purl.org/pe-repo/ocde/ford#1.06.15